Detection of prostate cancer using an electrochemical sensor integrated with molecular imprinting technology and ionic liquid: a novel approach - Wong, Ademar; Zeb, Shakeel; Santos, Anderson M.; Feitosa, Maria H. A.; Khan, Sabir; Moraes, Fernando C.; Sotomayor, Maria Del Pilar Taboada (Springer, 2024)
Carbon paste electrodes have been used for decades in electro-analytical screening, with numerous advancements in modifying electrochemical properties. Different materials have been utilized in various applications, encompassing electroanalytical techniques and healthcare sensing. The current research addresses the enhancement of the carbon paste electrode with ionic liquid and molecularly printed polymers for sensitive and selective detection of the sarcosine biomarker. The materials were characterized using their structural and morphological properties, and the roughness and surface area of the polymer were evaluated. The electrochemical response for sarcosine was obtained at a potential of 1.2 V by modifying the carbon paste electrode with ionic liquid and magnetic molecularly imprinted polymers (mMIPs). Under optimized conditions, the proposed method showed a concentration linear range of 2.0 × 10−7 to 1.04 × 10−4 mol L−1 and a low detection limit of 5.1 × 10−8 mol L−1. Aiming to demonstrate the efficiency of the proposed sensor, tests with biological samples were performed. The results showed robust recovery of sarcosine, ranging between 96 to 104% at two different concentration levels, affirming the efficacy of this method in determining sarcosine.
Detecção de câncer de próstata usando sensor eletroquímico integrado com tecnologia de impressão molecular e líquido iônico: uma nova abordagem
Keywords: Imprinted polymers; Sarcosine; Electrochemical sensors; Ionic liquids; Biological samples; Polímeros impressos; Sarcosina; Líquidos iônicos